Light microscopy and scanning electron microscopy of bacterial colonies isolated from ras malai samples from different markets of Lahore, Pakistan. Issue 11 (7th September 2020) - Shaheen, Shabnum; Khan, Palwasha; Sadia, Sehrish; Jaffer, Mehwish; Khalid, Sana; Siddique, Riffat; Mukhtar, Hanan; Iftikhar, Tehreema; Sarwar, Samina; Ilyas, Sobia; Khan, Farah
Abstract: The current study investigates the total bacterial contamination in various packed and unpacked ras malai samples of 14 different localities of Lahore, Pakistan. The bacterial colonies such as Bacillus sp. and Gamella sp. were isolated from ras malai samples and grown on agar‐broth media under sterile environmental conditions. Serial dilution technique was used to compose the replicates to get a viable count of bacteria in the samples. Results indicated that in case of packed ras malai samples, maximum bacterial count was observed in Sample 1 (422 × 10 −2 to 402 × 10 −6 ) and minimum bacterial count was in Sample 4 (21 × 10 −2 to 9.3 × 10 −6 ). For unpacked ras malai samples, maximum bacterial count was in Sample 3 (200.3 × 10 −2 to 181.3 × 10 −6 ) and minimum bacterial count was observed in Sample 1 (110 × 10 −2 to 90.4 × 10 −6 ). It was concluded that the marketed samples contain more bacterial count as compared to the standard sterilization values. Such products could possibly become the cause of many health problems in children. Abstract :